2013
DOI: 10.1681/asn.2012050526
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Regulation of Wnt Signaling through the Primary Cilium

Abstract: The primary cilium is a highly conserved environmental sensor and modulator of fluid movement in tubular structures. The growing recognition of mutations among its many components has led to the discovery of new disorders collectively called ciliopathies. Ciliary dysfunction disturbs a variety of signaling pathways along its basal body and axoneme that are critical for embryonic development and cell and organ homeostasis. Among the many pathways, here we discuss the emerging role of Wnt proteins in morphogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 66 publications
2
65
0
Order By: Relevance
“…4A,B) (Montcouquiol et al 2003;May-Simera and Kelley 2012;Cui et al 2013). Other studies also showed a role for cilia as a switch that can constrain canonical versus noncanonical Wnt signaling (Ross et al 2005;Simons et al 2005;Barrow et al 2007;Gerdes et al 2007;Corbit et al 2008;Huang and Schier 2009;Stottmann et al 2009;Lienkamp et al 2012;Oh and Katsanis 2013). However, the precise mechanism by which cilia regulate Wnt signaling is not well understood.…”
Section: Role Of Wnt Signaling In Cardiac Development and Chdmentioning
confidence: 99%
“…4A,B) (Montcouquiol et al 2003;May-Simera and Kelley 2012;Cui et al 2013). Other studies also showed a role for cilia as a switch that can constrain canonical versus noncanonical Wnt signaling (Ross et al 2005;Simons et al 2005;Barrow et al 2007;Gerdes et al 2007;Corbit et al 2008;Huang and Schier 2009;Stottmann et al 2009;Lienkamp et al 2012;Oh and Katsanis 2013). However, the precise mechanism by which cilia regulate Wnt signaling is not well understood.…”
Section: Role Of Wnt Signaling In Cardiac Development and Chdmentioning
confidence: 99%
“…By these means, primary cilia control cellular processes during development and in the adult organism. 20,[27][28][29][30][31][32][33][34][35][36] In addition, specialized non-motile sensory cilia are present on neurons in the olfactory epithelium of the nasal Table 1. Common types of congenital heart defects Congenital heart defect Abbreviation Characteristics…”
Section: Cilia Ciliopathies and Chd-an Overviewmentioning
confidence: 99%
“…2,189,192,193,196 The link between Wnt signaling and the primary cilium is highly controversial. 32,35,197 However, many Wnt signaling components, such as Fz3, Dvl, and β-catenin, localize to the ciliary/centrosomal axis, and dysregulated Wnt signaling has been reported in cells and tissues with disrupted ciliogenesis or basal body integrity. [198][199][200] Moreover, in the mouse inner ear, establishment of PCP was shown to depend on the formation of functional primary cilia.…”
Section: Cardiac Primary Cilia and Other Signaling Pathwaysmentioning
confidence: 99%
“…This has, in turn, suggested that phenotypes of ciliopathy patients might be attributed to defective paracrine signaling (1), including polydactyly due to defective sonic hedgehog (Shh) signaling (2) and renal cysts attributed to unbalanced Wnt signaling (3). Some data have raised the possibility that a fraction of these defects, especially Wnt, are driven by nonciliary functions of ciliary and basal body proteins (2,4); other findings have indicated that the cilium/basal body Wnt roles are likely specific to discrete spatiotemporal contexts (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%